Knowledge mapping of idiopathic scoliosis genes and research hotspots (2002-2022): a bibliometric analysis - Like Ru; Hong Zheng; Hong Zheng; Wenjun Lian; Shuying Zhao; Qimeng Fan (Frontiers Media S.A., 2023)
BackgroundThe etiology of idiopathic scoliosis (IS) remains unclear. Gene-based studies on genetic etiology and molecular mechanisms have improved our understanding of IS and guided treatment and diagnosis. Therefore, it is imperative to explicate and demarcate the preponderant areas of inquiry, key scholars, and their aggregate scholarly output, in addition to the collaborative associations amongst publications or researchers.MethodsDocuments were retrieved from the Web of Science Core Collection (WoSCC) with the following criteria: TS = ("idiopathic scoliosis" AND gene) refined by search operators (genomic OR "hereditary substance" OR "germ plasm" OR Cistrons OR genetics OR genetic OR genes OR Polygenic OR genotype OR genome OR allele OR polygenes OR Polygene) AND DOCUMENT TYPES (ARTICLE OR REVIEW), and the timespan of 2002-01-01 to 2022-11-26. The online bibliometric analysis platform (bibliometric), bibliographic item co-occurrence matrix builder (BICOMB), CiteSpace 6.1. R6 and VOS viewer were used to evaluate articles for publications, nations, institutions, journals, references, knowledge bases, keywords, and research hotspots.ResultsA total of 479 documents were retrieved from WoSCC. Fourty-four countries published relevant articles. The country with the most significant number of articles was China, and the institution with the most significant number of articles was Nanjing University. Citation analysis formed eight meaningful clusters and 16 high-frequency keywords. (2) The citation knowledge map included single nucleotide polymorphisms, whole exome sequencing, axonal dynamin, drug development, mesenchymal stem cells, dietary intake, curve progression, zebrafish development model, extracellular matrix, and rare variants were the current research hotspots and frontiers.ConclusionsRecent research has focused on IS-related genes, whereas the extracellular matrix and unusual variants are research frontiers and hotspots. Functional analysis of susceptibility genes will prove to be valuable for identifying this disease.